# Find and correct the errors in the statement: (2a + 3b)(a - b) = 2a^{2} - 3b^{2}

**Solution:**

An equation is a mathematical statement with an 'equal to' symbol between two algebraic expressions that have equal values.

Given,

(2a + 3b)(a - b) = 2a^{2} - 3b^{2}

Solving LHS we get,

(2a + 3b)(a - b)

= (2a × a) - (2a × b) + (3b × a) - (3b × b)

= 2a^{2} - 2ab + 3ab - 3b^{2}

= 2a^{2} + ab - 3b^{2}

But, RHS is given as 2a^{2} - 3b^{2}

Thus, L.H.S ≠ R.H.S

The correct statement is (2a + 3b)(a - b) = 2a^{2} + ab - 3b^{2}

**Video Solution:**

## Find and correct the errors in the statement: (2a + 3b)(a - b) = 2a² - 3b²

### Class 8 Maths NCERT Solutions - Chapter 14 Exercise 14.4 Question 13

**Summary:**

Find and correct the errors in the statement: (2a + 3b)(a - b) = 2a^{2} - 3b^{2}. The correct statement is (2a + 3b)(a - b) = 2a^{2} + ab - 3b^{2}